Meta-Analysis of Green Roof Performance Parameters and Policy Readiness in Tropical Indonesia - Fajri Gumilang (BRIN Publishing (Penerbit BRIN), 2026)
Abstrak Urbanisasi pesat di Indonesia memperburuk urban heat island (UHI) dan degradasi lingkungan perkotaan. Penelitian ini mengevaluasi efektivitas atap hijau sebagai instrumen kebijakan pembangunan perkotaan berkelanjutan di wilayah tropis, sekaligus menjadi acuan regulasi seperti di Singapura. Pendekatan integratif multitahap digunakan melalui systematic literature review (SLR) berbasis PRISMA 2020 (2020–2025), meta-analisis kuantitatif 20 parameter operasional, dan analisis siklus kebijakan, dengan data ditriangulasi dari Scopus, ScienceDirect, dan Google Scholar untuk memetakan korelasi kinerja teknis dan kesiapan regulasi. Hasil menunjukkan atap hijau menawarkan keunggulan ganda, meningkatkan ketahanan lingkungan dan efisiensi biaya jangka panjang dibanding sistem fotovoltaik surya. Evaluasi difokuskan pada kinerja termal (penurunan suhu ruang hingga 13,14 °C; pengurangan beban pendinginan ±40%), mitigasi hidrologi (retensi air hujan 85,7%), serta fungsi sosial-spasial melalui pertanian perkotaan dan ketahanan pangan. Implementasi di Indonesia masih terfragmentasi akibat ketiadaan standar bangunan wajib dan minim insentif finansial. Transformasi pedoman teknis menjadi regulasi nasional yang mengikat, didukung pemetaan berbasis SIG, menjadi prasyarat strategis untuk transisi kota tangguh iklim dan pengambilan kebijakan perkotaan berkelanjutan. Abstract In Indonesia, rapid urban growth has worsened the urban heat island effect and led to more environmental degradation from urban areas. This study evaluates how green roofs are a sustainable urban development policy instrument in tropical regions while also providing a regulatory benchmark for comparison against Singaporean green roof practices. An integrative multi-phase approach was taken using a PRISMA 2020-based systematic literature review (2020-2025), quantitative meta-analysis of twenty operational parameters, and policy cycle analysis. The data sources were triangulated between Scopus, Science Direct, and Google Scholar to identify correlations between technical performance and regulatory readiness for green roofs. Findings for green roofs suggest that they provide dual benefits via improved environmental resilience and much greater long-term cost effectiveness compared to photovoltaic solar panels. The evaluation reviews three areas of impact: thermal performance (reduction of indoor temperatures up to 13.14 °C and cooling loads by approximately 40%), hydrological mitigation (rainwater retention up to 85.7%), and socio-spatial benefits through urban agriculture and food security. However, implementation of green roofs in Indonesia remains fragmented due to a lack of mandatory building codes and an absence of significant financial incentives to promote widespread adoption. Transforming technical guidelines into binding national regulations, supported by GIS-based spatial mapping, constitutes a strategic prerequisite for advancing climate-resilient cities and evidence-based sustainable urban policymaking.